An Analysis of Deixis and Speech Act Used in English Teaching and Learning Process - Yulfi Yulfi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
This study focuses on analyzing deixis and speech acts used by the English teacher and eleventh grade students of language program at Islamic Integrated Senior High School Curup in the academic year 2013/2014. The topic was chosen by the researcher as the object of the research, first of all because deixis and speech acts are commonly analyzed in the daily conversation such as in movie and comic. Secondly, this school is the one that has a language program class at eleventh grade besides two science program classes and two social program classes. This study means to explain the used of deixis and speech acts in English teaching and learning. The design of this research is an ethnography research and the main instrument of this research is the researcher itself. The finding of this study shows that the teacher of English and students used deixis in their daily activity in the classroom. However, the most frequently types of deixis used by them is person deixis. Further, the most dominant type of speech acts on English teaching and learning at this class is directive utterance. Generally, the teacher more often used them to give command, suggestion and request.The teacher and students used deixis and speech acts almost in every moment. Because this class used teacher center, so the students used deixis and speech act only when they responded the teachers questions. Key words: deixis, speech acts, directive utterance, person deixis.